IDENTIFICATION OF WORM SOIL TRANSMITTED HELMINTHES VEGETABLES IN THE HOUSE EATING TELAGA REGION GORONTALO DISTRICT - Fatrawaty Baruadi; Laksmyn Kadir; Adnan Malaha (Journal of Health, Technology and Science (JHTS), 2021)
Worms is a health problem that is still widely found throughout the world. Based on data from (WHO), more than 1.5 billion people or 24% of the population are infected with Soil Transmitted Helminthes (STH), Soil Transmitted Helminthes is a group of parasitic worms (Nematode class) that can causes infection in humans through contact with eggs or parasite larvae that develop in moist soil, one type of vegetable that is often contaminated by Soil Transmitted Helminths (STH) is cabbage, cabbage (Brassica olerecea) is a vegetable that is generally consumed raw because it is seen from the the texture and organoleptic of this vegetable allows it to be used as fresh vegetables. The purpose of this study was to identify the eggs of Soil Transmitted Helminthes (STH) worms in cabbage at the Telaga Regional Restaurant, Gorontalo District. Using the sedimentation method, this research is a quantitative descriptive study with a total sample of 15, using a microscope then the data is presented in tabular form and reported in percentage form using the frequency distribution formula. The results showed that from 15 samples of cabbage that were examined 1 was positive with a percentage rate of 6.67%. It is hoped that the community, especially cabbage vegetable farmers and sellers of fresh vegetables, can improve the hygiene and cleanliness of vegetables (fresh vegetables) so that they are free from microorganisms, especially STH eggs, so that the prevention of worm infection can be done.